Motivasi dan Perilaku Wisatawan di Desa Wisata Nglanggeran Menurut Prinsip Ekowisata - Kinasih, Ailsa (Gadjah Mada Journal of Tourism Studies, 2025)
Nglanggeran Tourism Village is an ecotourism destination located in Patuk, Gunungkidul, within the Special Region of Yogyakarta.  The objective of ecotourism development is to save the environment while enhancing the local economy.  In 2014, the influx of visitors to Nglanggeran Tourism Village surged, resulting in ecological harm due to insufficient environmental awareness among tourists.  In 2015, Pokdarwis aimed to decrease visitor numbers by raising ticket prices to attract tourists ready to pay more for a superior tourism experience.  This study seeks to investigate the motivations and behaviors of tourists in Nglanggeran Tourism Village and assess if these align with the ideals of ecotourism.  The research utilizes the motivation and behavior paradigm established by Anishchenko (2016), encompassing two dimensions: motivation aligned with ecotourism principles and personal motivation.  The study used a descriptive quantitative methodology with a total of 100 respondents as samples.  The findings reveal that visitors to Nglanggeran Tourism Village are influenced by both categories of motivation; still, personal motivation receives the highest rating at 4.14, surpassing motivation aligned with ecotourism principles, which scores 4.10.  Moreover, tourist behavior concerning the acquisition of local products and services, along with a preference for traveling in small groups, is predominantly influenced by personal motivations.  The propensity of tourists to purchase local products and services remains comparatively low